Solidaridades afromestizas: compadrazgo y padrinazgo entre la población de sangre africana en el primer libro de bautizos de Cartago (1594-1680) - Eduardo Madrigal (Caravelle)
This article deals with the relationship of spiritual kinship in the colonial province of Costa Rica in the 17th century. By studying the first book of baptisms of its colonial capital, Cartago City, we come to the conclusion that this was the result of interaction between all socio-ethnic groups in colonial society, allowing them to weave multiple relationships, but that it might as well have corresponded to the colonial authorities’ interest to maintain the social distances prevailing at the time.